A linear lattice model for polyglutamine in CAG-expansion diseases - Bennett, Melanie J. (The National Academy of Sciences, 2002)
Huntington's disease and several other neurological diseases are caused by expanded polyglutamine [poly(Gln)] tracts in different proteins. Mechanisms for expanded (>36 Gln residues) poly(Gln) toxicity include the formation of aggregates that recruit and sequester essential cellular proteins [Preisinger, E., Jordan, B. M., Kazantsev, A. & Housman, D. (1999) Phil. Trans. R. Soc. London B 354, 1029–1034; Chen, S., Berthelier, V., Yang, W. & Wetzel, R. (2001) J. Mol. Biol. 311, 173–182] and functional alterations, such as improper interactions with other proteins [Cummings, C. J. & Zoghbi, H. Y. (2000) Hum. Mol. Genet. 9, 909–916]. Expansion above the “pathologic threshold” (≈36 Gln) has been proposed to induce a conformational transition in poly(Gln) tracts, which has been suggested as a target for therapeutic intervention. Here we show that structural analyses of soluble huntingtin exon 1 fusion proteins with 16 to 46 glutamine residues reveal extended structures with random coil characteristics and no evidence for a global conformational change above 36 glutamines. An antibody (MW1) Fab fragment, which recognizes full-length huntingtin in mouse brain sections, binds specifically to exon 1 constructs containing normal and expanded poly(Gln) tracts, with affinity and stoichiometry that increase with poly(Gln) length. These data support a “linear lattice” model for poly(Gln), in which expanded poly(Gln) tracts have an increased number of ligand-binding sites as compared with normal poly(Gln). The linear lattice model provides a rationale for pathogenicity of expanded poly(Gln) tracts and a structural framework for drug design.